2014
DOI: 10.3390/nu6052088
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Sugar-Sweetened Beverages Is Associated with Components of the Metabolic Syndrome in Adolescents

Abstract: Sugar-sweetened beverages (SSBs) are the principle source of added sugar in diets. Cardiometabolic disturbances can occur from early childhood to adulthood. The aim of this cross-sectional study was to examine the gender-specific association of SSB intake with metabolic syndrome (MetS) and its components among adolescents in Taiwan. A total of 2727 adolescents aged 12 to 16 years randomly selected from three diverse economic areas in Southern Taiwan by using a multistage-sampling strategy participated in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(150 citation statements)
references
References 38 publications
7
134
0
9
Order By: Relevance
“…84 Observational studies have found that sugar-sweetened beverages are associated with type 2 diabetes, abdominal obesity, and the metabolic syndrome. [85][86][87][88][89] Stronger associations are noted in larger studies of longer duration, 90,91 and systematic reviews and metaanalyses corroborate these adverse effects. 85,[92][93][94] Even 100% fruit juice (although technically not a sugar-sweetened beverage) provides high concentrations of fructose, removed from its usual biological context (eg, whole fruit).…”
Section: Basic Science Datamentioning
confidence: 91%
“…84 Observational studies have found that sugar-sweetened beverages are associated with type 2 diabetes, abdominal obesity, and the metabolic syndrome. [85][86][87][88][89] Stronger associations are noted in larger studies of longer duration, 90,91 and systematic reviews and metaanalyses corroborate these adverse effects. 85,[92][93][94] Even 100% fruit juice (although technically not a sugar-sweetened beverage) provides high concentrations of fructose, removed from its usual biological context (eg, whole fruit).…”
Section: Basic Science Datamentioning
confidence: 91%
“…14 Advertisement characteristics were compared across target audiences, and airtime for advertisements by target audience were presented by food and beverage type. Given the health concerns related to sugarsweetened beverage consumption among children, [15][16][17][18] we present a case study to describe the marketing approaches used in promoting sugar-sweetened beverages. The results provide novel information about the nature and extent of parent-directed advertising for nutritionally questionable children's foods and beverages on television.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Studies have shown that high consumption of SSB is linked not only to obesity [34,42] but also to metabolic syndrome [43], type 2 diabetes [4], as well as cardiovascular diseases [5]. The consumption of 455 ml of SSB for 6 months was associated with lipid accumulation in the liver, muscle and visceral fat [44].…”
Section: Ssb Overconsumption Chronic Diseases and Obesitymentioning
confidence: 99%